Improvement of study process of mathematics in Vilnius College in higher education - Saldauskienė, Jovita; Virkutis, Vytautas (Lietuvos matematikos rinkinys, 2005)
There are investigated the problems of mathematics computing, problems of assessment strategy in this article. There are also analyzed the improvement of study process as well as the improvement of computing and trainings in the mathematics lessons. It was made the comparative research of the first-year students' advancement of mathematics’ subject as well as the research of students' opinion.There are made the following conclusions:1. The chosen model for teaching mathematics subject in Vilnius College in Higher Education is effective.2. The computing for mathematics lessons and trainings is purposive to apply.3. It is recommended constantly advise students especially that ones who are less prepared for the studies.4. It is purposive to make students’ teams to do independent students' work.5. It is necessary to continue the researches, to gain further experience and keep working on the improvement of the teaching methodic on the mathematics with computing.
Keywords: mathematics; study process; students